PENGARUH WORK LIFE BALANCE, WORK ENGAGEMENT, DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN DI MUSTIKARASA CAFE & RESTO GRESIK - Zahroh, Riris Amaliatus; Khasanah, Uswatun (Jurnal Ekonomi dan Kewirausahaan Kreatif, 2024)
This study aims to research the influence of work life balance, work engagement, and job satisfaction on employee performance at Mustikarasa Café & Resto Gresik. This study is a qualitative research that uses Partial Least Square (PLS) Structure Equation Modelling (SEM) analysis. The statistical tool used in this study is Warp-PLS. The respondents in this study were 52 employees who worked at Mustikarasa Café & Resto Gresik. The results of this study explain that work-life balance does not affect employee performance. In contrast to work engagement, it reduces employee performance and job satisfaction can improve employee performance at Mustikarasa café & resto Gresik.